-x+5x-6=0 -2x-10x-12=0 x+x-6=0

-x+5x-6=0 -2x-10x-12=0 x+x-6=0

  • -x+5x-6=0
    -x+5x=6
    4x=6
    x=6/4

    Simplificando x=3/2
    —————————————————————————————————————————
    -2x-10x-12=0
    -12x=12 .(-1)
    12x=-12
    x=-12/12
    x=-1
    —————————————————————————————————————————
    x+x-6=0
    2x=6
    x=6/2
    x=3

    Ab .

  • — x + 5x — 6 = 0
    4x — 6 = 0
    4x = 6
    x = 6/4
    x = 3/2

    -2x — 10x — 12 = 0
    — 12x = 12
    x = — 1

    x + x — 6 = 0
    2x = 6
    x = 3

    Com: — x + 5x — 6 = 0

    = b — 4ac
    = 1 — 4. 5 . (-6)
    = 1 + 120 = 121

    x = 1 + 11 = 12/ -2 = — 6
    — 2
    x» = 1 — 11 = -10/ -2 = 5
    — 2
    x = — 6 e x = 5

    Com
    — 2x — 10x — 12 = 0
    (dividir por 2)

    — x — 5x — 6 = 0
    = 25 — 4 (-1) (-6)
    = 25 — 24
    = 1

    x =
    — (-5) + 1 = 5 + 1 = — 3
    — 2 — 2

    x = — (-5) — 1 = 4= — 2
    -2 -2

    x = -3 ;x = — 2

    c)
    x + x — 6 = 0

    = b — 4ac = 1 — 4.1 (-6) = 25

    x = — 1 +5= 4/2 = 2
    2

    x = — 1 — 5 = — 6/2 = — 3
    2

    x = 2 e x = — 3


Добавить комментарий

17 − 15 =